2010
DOI: 10.1161/strokeaha.110.588046
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Randomized Controlled Trial of a Patient and General Practitioner Intervention to Improve the Management of Multiple Risk Factors After Stroke

Abstract: Background and Purpose-Stroke is a major public health concern worldwide and survivors remain at high risk of recurrence. Secondary prevention requires management of multiple risk factors but current management is suboptimal. Evidence of the effectiveness of interventions to improve poststroke risk factor management from well-designed trials is limited. We assessed the effectiveness of a patient and general practitioner systematic follow-up intervention to improve risk factor management after stroke. Methods-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(108 citation statements)
references
References 29 publications
(42 reference statements)
2
106
0
Order By: Relevance
“…However, our study setting closely resembles the United Kingdom National Health Service and integrated managed care organizations in the United States, and the clinical profiles of our participants were similar to recent reports of stroke survivors from other Canadian provinces, the US, the UK and Europe. 1,2,10,20,24,25,28 When considering the external validity of our results, the under-treatment of vascular risk factors is a nearly universal phenomenon and has been documented in many other settings and for other atherosclerotic conditions.…”
Section: Secondary Outcomesmentioning
confidence: 76%
See 1 more Smart Citation
“…However, our study setting closely resembles the United Kingdom National Health Service and integrated managed care organizations in the United States, and the clinical profiles of our participants were similar to recent reports of stroke survivors from other Canadian provinces, the US, the UK and Europe. 1,2,10,20,24,25,28 When considering the external validity of our results, the under-treatment of vascular risk factors is a nearly universal phenomenon and has been documented in many other settings and for other atherosclerotic conditions.…”
Section: Secondary Outcomesmentioning
confidence: 76%
“…23 Indeed, several other studies have also found minimal benefit if case management only involves monitoring of risk factors, patient counselling and feedback to patients and/or primary care physicians. 14,16,24,25 Limitations Our trial was too short and was underpowered to detect changes in clinical events. However, the outcomes we evaluated (systolic blood pressure and cholesterol levels) are well-validated predictors of subsequent stroke and cardiovascular events, and there is a robust evidence base supporting blood pressure and lipid optimization for secondary prevention, making a very large outcomes-driven trial unnecessary, in our opinion.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…4 The study also found no statistical significance; however, during the study, the United Kingdom Department of Health introduced quality and outcome measure strategies. Investigators believe these skewed the results, as the health care professionals were impacted by this change, and this was not accounted for in the original design of the study.…”
Section: Standardized Discharge Ordersmentioning
confidence: 90%
“…Longer term observational studies have indicated that compliance with medication adherence declines 1 year 37 and 2 years 38 after stroke. Furthermore, the Stop Stroke intensive intervention described by Wolfe et al, 39 which aimed at reducing secondary stroke risk, resulted in no signifi cant differences for participants in the intervention group on the key outcomes of antihypertensive therapy, antiplatelet therapy treatment, or smoking cessation at 12 months.…”
Section: Follow-upmentioning
confidence: 98%